Micro, Small, and Medium Enterprises Eligibility and Financial Institutions Selection for Provision Capital - Sutanto, Yusuf; Purnama, Bambang Eka; Rapiyanta , Paulus Tofan (International Journal of Business, Law, and Education, 2025)
Some of the obstacles to Micro, Small, and Medium Enterprises (MSMEs) existence include difficulty in obtaining additional capital from banking institutions due to lack of employee knowledge and unfulfilled requirements. This research purpose is to determine MSMEs feasibility and  selection of appropriate financial institutions to apply for additional capital using a decision support system. There are 25 MSMEs samples in Karanganyar City to be used as research material. Decision tree algorithm is used to calculate initial decisions in specify MSMEs suitability to be given capital. AHP method is used as final decision to decide an appropriate financial institution to carry out additional capital. Accuracy level testing decision tree algorithm implementation to determine MSMEs feasibility resulted in 86.67%. Accuracy level of testing AHP method to decide financial institutions suitability resulted in 76.91%. From the test results, it can be concluded that  developed system is good or accurate.